Influence of different preoperative fasting times on women and neonates in cesarean section: a retrospective analysis - Yi Li; Danchen Su; Yijuan Sun; Zurong Hu; Zaomei Wei; Jie Jia (BMC, 2019)
Abstract Background This study was to evaluate the impact of different preoperative fasting conditions on women and neonates through a retrospective analysis. Methods A total of 1599 women were divided into 5 groups according to different preoperative fasting times: group A: solid food ≥8 h; clear fluids ≥6 h; B: solid food ≥8 h; clear fluids ≥2 h < 6 h; C: solid food ≥6 h < 8 h; clear fluids < 2 h; D: solid food ≥2 h < 6 h; clear fluids < 2 h; E: solid food < 2 h; clear fluids < 2 h. Results Incidence rate of vomiting of women was lower in group C (solid food ≥6 h < 8 h and clear fluids < 2 h) than other groups (P <  0.05). Compared with the fasting for a long time (groups A and B: solid food > 8 h and clear fluids > 2 h at least), the incidence rate of hypoglycemia and acidosis of neonates in group C displayed a certain decrease (P <  0.05). Although shorter fasting times (solid food < 6 h at least) reduced the incidence of hypoglycemia and acidosis in neonates, it increased the risk of vomiting of women. Conclusion The preoperative fasting of solid food ≥6 h < 8 h and clear fluids < 2 h reduces the incidence of vomiting in women's anesthesia and the risk of hypoglycemia and acidosis in neonates.